Etnobotani Tumbuhan Obat Masyarakat Etnis Buton : Etnobotani Tumbuhan Obat Masyarakat Etnis Buton - Alvina Yulianti Tan; Syamsiah, Syamsiah; Hiola, St. Fatmah (Jurnal Biotek, 2022)
Ethnobotany is the science that studies the use of various plants by people living in an area, one of which is traditional medicine. This study aimed to determine the species of medicinal plants, ways to prepare them, and the diseases that can be treated with the plants by the Butonese community in Baubau. This research was descriptive and exploratory with survey methods and interview techniques to provide a detailed description of the use of medicinal plants by the Butonese community. The sampling method used was snowball sampling, where the interview was conducted in an open-ended form by referring to the interview table. The research showed that the Butonese community used 41 different plants as medicinal plants. All the plant organs are used, like leaves, fruits, seeds, stems, rhizomes, tubers, and roots. There are ten ways to prepare medicinal plants and six ways to use medicinal plants. Fever, cough, ulcers, wounds, and various internal diseases, such as diabetes, hypertension, and cancer, are among the illnesses that can be treated with these medicinal plants.